Effects of high-intensity inspiratory muscle warm-up on high-intensity exercise performance and muscle oxygenation - Koizumi, J.; Ohya, T. (International Journal of Sports Physiology and Performance, 2024)
Purpose: An inspiratory muscle warm-up (IMW) improves inspiratory muscle function, but the effects of high-intensity exercise are inconsistent. We aimed to determine the effects of high-intensity IMW on high-intensity exercise performance and muscle oxygenation.